Efficacy and safety of fractional CO2 laser therapy combined with triamcinolone acetonide injection for hypertrophic scar: a preliminary systematic review and meta-analysis - Zhang, Jianfeng; Wu, Mengke; Liu, Cong; Zhu, Xiaochen; Guo, Qin; Tan, Cheng (Frontiers in Medicine, 2026)
BackgroundThis study aims to systematically evaluate the efficacy and safety of fractional CO2 laser therapy combined with triamcinolone acetonide (TA) injection for hypertrophic scar (HS).Materials and methodsRandomized controlled trials (RCTs) investigating the combination therapy of fractional CO₂ laser and TA injection for HS were identified through systematic searches of PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, Sinomed, and VIP databases from inception to December 2024. The risk of bias was assessed using the Cochrane Collaboration’s Risk of Bias tool. Meta-analysis was performed with RevMan (version 5.3), while sensitivity analysis and publication bias assessment were conducted using Stata (version 14.0). The quality of evidence for outcomes was evaluated with the Grades of Recommendations, Assessment, Development, and Evaluation (GRADE) assessment.ResultsNineteen studies involving 1,775 patients were included in this meta-analysis. Compared with TA injection alone, the pooled results showed that fractional CO₂ laser combined with TA injection significantly reduced Vancouver Scar Scale scores [MD: −2.52, 95% CI: −3.07 to −1.98, p < 0.00001], pruritus scores [MD: −0.86, 95% CI: −0.94 to −0.78, p < 0.00001], pain scores [MD: −1.04, 95% CI: −1.38 to −0.71, p < 0.00001], scar thickness [SMD: −2.36, 95% CI: −3.12 to −1.61, p < 0.00001], serum TGF-β1 level [SMD: −2.09, 95% CI: −2.71 to −1.46, p < 0.00001], serum VEGF level [SMD: −2.03, 95% CI: −2.90 to −1.17, p < 0.00001], serum EGF level [MD: −17.38, 95% CI: −20.94 to −13.82, p < 0.00001], and serum TNF-α level [SMD: −1.81, 95% CI: −2.77 to −0.85, p = 0.0002]. Regarding safety, the combination of fractional CO₂ laser and TA injection reduced the incidence of skin atrophy [RR: 0.52, 95% CI: 0.34 to 0.80, p = 0.003] compared to TA injection alone. There was no significant difference between the two groups in the incidence of adverse events, including folliculitis [RR: 0.64, 95% CI: 0.30 to 1.35, p = 0.24], erythematous edema [RR: 1.21, 95% CI: 0.68 to 2.16, p = 0.52], skin allergies [RR: 0.38, 95% CI: 0.14 to 1.05, p = 0.06], pigmentation [RR: 1.12, 95% CI: 0.58 to 2.16, p = 0.73], ulcers [RR: 0.35, 95% CI: 0.11 to 1.16, p = 0.09], infections [RR: 1.45, 95% CI: 0.29 to 7.17, p = 0.65], and blisters [RR: 0.33, 95% CI: 0.01 to 7.88, p = 0.50].ConclusionPreliminary evidence suggests that fractional CO₂ laser combined with TA injection is an effective treatment for HS. However, due to methodological limitations in the included studies, large-scale, rigorously designed RCTs are required to validate these findings. Additionally, all 19 RCTs were conducted in China with Chinese participants; therefore, the current evidence is limited to this population and requires validation in other ethnic groups.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025630116, identifier PROSPERO (CRD4202563011).